Monitoring of selected mycotoxins in maize and grass silages - Selwet, Marek (Polish Journal of Agronomy, 2022)
The research aimed to quantify the occurrence of se- lected mycotoxins: AFB1 (aflatoxin B1), DON (deoxynivalenol) and ZEN (zearalenone) in maize and grass silages. The silage was prepared in foil bales without the addition of differentiating factors. Silages derived from 36 farms located in Wielkopolskie voivodeship. The total number of mould fungi and the pH value were determined in the collected samples. The level of contami- nation with selected mycotoxins was determined by high-perfor- mance liquid chromatography (HPLC). Based on the obtained results, it was found that the total number of mould fungi in the examined silage samples was in the range 5.00–6.90 log CFU g-1 fresh weight, pH value in the range 3.34–4.73. It was shown that maize silage is more contaminated with mycotoxins than grass silage. In the tested samples, statistically significant differences (P <0.05) were found only for the mycotoxin ZEN. ZEN content was 74% higher in maize silage compared to grass silage. Con- tamination of silages with mycotoxins AFB1 and DON was at a similar level, and it was 4.22 and 354.14 μg kg-1 for maize and 4.98 and 330.25 μg kg-1 for grasses, respectively.